The Phoenix Rising Program - Merritt Hicks; Debe Franz (Adult Education Research Conference, 2011)
The Phoenix Rising Program is a Life Skills pilot program within the Work First Department at Edmonds Community College, in an urban community north of Seattle, Washington. It is specifically designed for women who are victims of domestic violence and receiving Temporary Aid for Needy Families (TANF) through the Department of Social and Health Services (DSHS). The goal of this program is to provide the educational support needed by these women to become stabilized and self-sufficient. Goal setting and career planning are essential components of this self-sufficiency program. Once family stability is achieved, the students transition either into academic or professional/technical training programs at a local college, or into living wage jobs.